“Estandarización del proceso de corte de tableros para el mejoramiento de su línea de producción, caso de estudio microempresa Herrajes y Tableros Pilatasig”. - Pilatasig Ilaquiche, German Ruben (2021)
The main of this project is to standardize the board cutting process and generate a plant distribution proposal for the future infrastructure of the microenterprise Herrajes y Tableros Pilatasig, through the application of several industrial engineering tools, such as multi-criteria analysis methods, plant distribution tools and movement time study in order to optimize the physical space and reduce unproductive times in the cutting process. The study began with the collection of information on the current situation of the microenterprise, through the collection of data related to the general and I got wrong one distribution of the plant was determined, which generated bottlenecks in the process. Next, an analysis was made of the times obtained from the sample was carried out for its respective standardization, note that the samples are taken before the redistribution of the plant was obtained where an average time of 28.55 minutes was obtained, a normal time of 29.40 minutes and finally a standard time of 33.52 minutes. Then we proceeded to generate plant layout alternatives through the application of the SLP (Systematic Layout Planning) methodology and the application of the constructor type algorithm (CORELAP), which was analyzed by means of the AHP (Analytic Hierarchy Process) multi-criteria analysis method to obtain the best option under certain criteria. The proposal generated in this research project will serve as a basis for the manager of the microenterprise Herrajes y Tableros Pilatasig so that in the future apply the new distribution of the plant with which it is desired to reduce downtime by 57.48% with respect to the current time.